Towards a Rational Balanced Pancreatic and Islet Allocation Schema. (9th November 2021) - Kandeel, Fouad; El-Shahawy, Mohamed; Singh, Gagandeep; Dafoe, Donald C.; Isenberg, Jeffrey S.; Riggs, Arthur D.
Allocation of donated organs for transplantation is a complex process that considers numerous factors such as donor, organ and candidate characteristics and practical issues such as geography. Whole pancreas and isolated islet transplantation are lifesaving for certain individuals with diabetes. Herein, we suggest a revised allocation schema that matches donor characteristics with candidate medical condition while allowing for geographic considerations. It is hoped that adoption of this schema will shorten allocation time, decrease organ waste and optimize the parity between organ donor characteristics and candidate state of health.